Failure mechanism analysis and reliability assessment of an aircraft slat. (February 2016) - Pang, Huan; Yu, Tianxiang; Song, Bifeng
Abstract: A slat is one of the most importance high-lift devices on an aircraft, whose performance influences the safety of an aircraft directly, and its failure may lead to serious consequence. This study focuses on the failure mechanism analysis and reliability assessment of the slat. Firstly, based on the work principle, FTA (failure tree analysis) and FMEA (failure modes and effect analysis) are used to analyze the potential failure modes and mechanism of failure modes. Secondly, simulation model is established using LMS Virtual.Lab and it is validated based on test data and mathematic model. Finally, the reliability and failure cases are assessed based on the results of dynamic simulation. The reliability analysis results show that transmission shaft fracture and motion seizure are the main failure modes. Failure assessment shows that the safety margin decreases to a very low value if transmission shaft fracture occurs, while a roller seized can lead to slat motion seizure. Highlights: Failure modes and failure mechanism of the slat are fully analyzed. Main failure modes of the slat are obtained. Dynamic responses of failure cases are investigated.